2008
DOI: 10.1007/s00442-008-1021-2
|View full text |Cite
|
Sign up to set email alerts
|

River hydrological seasonality influences life history strategies of tropical riverine fishes

Abstract: Under a particular set of selective forces, specific combinations of traits (strategies) will be favored in a given population, within the particular constraints of the considered species. For fishes, three demographic strategies have been suggested to result from adaptive responses to environmental predictability (i.e., seasonality): periodic, opportunistic and equilibrium [Winemiller KO, Rose KA (1992) Patterns of life-history diversification in North American fishes: implications for population regulation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
103
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(109 citation statements)
references
References 64 publications
5
103
0
1
Order By: Relevance
“…Nevertheless, the reproductive activity is intensified in June and July followed by December and January, and in some months there is a decrease in the proportion of reproducing females. The long reproductive period was also found by various authors in small-sized species (Mazzoni et al 2002(Mazzoni et al , 2005Hojo et al 2004), but not corresponding with a reproductive strategy for seasonal environments (Munro 1990;Vazzoler and Menezes 1992), characterized by species with a short reproductive period associated with the favorable conditions of flooding (Tedesco et al 2008), as reported for Moenkhausia sanctaefilomenae in the northern Pantanal (Lourenço et al 2008a). Furthermore, the long reproductive period shows a intraspecific variation in O. pequira, once Oliveira et al (2010) in studying the reproductive period of the same species in southern Brazil (sub-tropical region) found two reproductive steps, from September to October and from January to February.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Nevertheless, the reproductive activity is intensified in June and July followed by December and January, and in some months there is a decrease in the proportion of reproducing females. The long reproductive period was also found by various authors in small-sized species (Mazzoni et al 2002(Mazzoni et al , 2005Hojo et al 2004), but not corresponding with a reproductive strategy for seasonal environments (Munro 1990;Vazzoler and Menezes 1992), characterized by species with a short reproductive period associated with the favorable conditions of flooding (Tedesco et al 2008), as reported for Moenkhausia sanctaefilomenae in the northern Pantanal (Lourenço et al 2008a). Furthermore, the long reproductive period shows a intraspecific variation in O. pequira, once Oliveira et al (2010) in studying the reproductive period of the same species in southern Brazil (sub-tropical region) found two reproductive steps, from September to October and from January to February.…”
Section: Discussionmentioning
confidence: 55%
“…In fishes, a wide diversity in traits and patterns of life history has been documented (Winemiller 1989;Wootton 1998;Hutchings 2002;King et al 2003), which by way of high phenotypic plasticity varies intra-and interspecifically in response to environmental factors (Pampoulie et al 2000;Blanck and Lamouroux 2007;Tedesco et al 2008;Mérona et al 2009), altering size, growth, mortality, age and reproductive period (Wootton 1998;Lowe-McConnel 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The change in hydrological variability, a parameter known to significantly affect the representation of mean life history traits in fish communities (Tedesco et al 2008), was one of the most prominent transformations in the Petit-Saut Reservoir after its filling. Fish in the Sinnamary River before damning experienced large stochastic variations in discharge and water level and, as a consequence, opportunistic/periodic strategies dominated the community (Ponton and Mérona 1998).…”
Section: Reproductive Strategiesmentioning
confidence: 99%
“…Balcombe et al 2006). Tedesco et al (2008) also reported that floodplain inun dation can enhance recruitment by improving the feeding environment for larvae, resulting in clear responses to hydrological seasonality in tropical river populations. Thus, in the warm season prey may be more abundant or move more on the currents of flowing water, allowing freshwater predators to remain in one location and ambush prey that move into or through an area.…”
Section: Discussionmentioning
confidence: 97%